A Case Report: Pseudoangiomatous Stromal Hyperplasia Tumor Presenting as a Palpable Mass - Vo, Q. D.; Koch, G.; Girard, J. M.; Zamora, L.; Bouquet de Jolinière, Jean; Khomsi, F.; Feki, A.; Hoogewoud, H. M. (Frontiers in Surgery, 2016)
We report a case of woman with a palpable lump on her left breast. On mammography a huge mass located between the inner and outer inferior breast quadrants of the left breast was found. The ultrasound examination realized later revealed a heterogeneous mass with smooth and lobulated borders. A MRI was also performed, showing an oval mass with heterogeneous areas of enhancement. Finally a core biopsy under sonographic guidance revealed a pseudo angiomatous stromal hyperplasia of the breast (PASH).